The EU Framework for the Screening of Foreign Direct Investment as a Response to the Belt and Road Initiative in the Post-COVID Era - Jakub Kociubiński (Studia Europejskie, 2023)
After the limbo caused by the COVID-19 pandemic, Chinese investments have picked up in the ﬁrst quarter of 2023. Investments through China’s Belt and Road Initiative are carried out by approaching potential participants individually, or via dedicated platforms outside the EU’s legal and institutional framework. Thus, the EU Framework for the Screening of Foreign Direct Investment – which is likely to get its so-called “baptism of ﬁre” after its COVID-induced hibernation – can be seen as an implicit response to said Chinese initiative. This framework should be considered a message directed simultaneously towards foreign actors, discouraging them from attempting to carry out investments in the EU with the intention of bypassing the relevant European rules, and also towards Member States, cautioning them against facilitating such operations. The author will argue that the regulatory model has too many in-built unknowns that could prevent the framework from achieving its objectives.